Notes on the genus Larnaca Walker, 1869 (Orthoptera: Gryllacridinae) from China - Du, Baojie; Bian, Xun; Shi, Fuming (Zootaxa, 2017)
Walker (1869) proposed the genus Larnaca with type species Larnaca fasciata Walker, 1869. Karny (1937) gave the characters of the genus and listed 8 species. Gorochov (2003) subdivided the genus into two subgenera: Larnaca and Paralarnaca, and their type species are Larnaca (Larnaca) fasciata Walker, 1869 (Malesia) and Larnaca (Paralarnaca) johni (Griffini, 1911) (Malesia) respectively, and described 2 new species, i.e. Larnaca (Larnaca) vietnamensis Gorochov, 2003 (type locality: Vietnam) and Larnaca (Larnaca) phetchaburi Gorochov, 2003 (type locality: Thailand). Bian et al. (2015) firstly reported Larnaca Walker, 1869 from China, and described 1 new species, i.e. Larnaca (Larnaca) emarginata Bian, Guo & Shi, 2015. So far, the genus Larnaca includes 13 species.